Oscillation Сentre Сontrol of the Оscillating Мotor-Сompressor - Kudarauskas, S.; Senulis, A.; Simanynienė, L. (Elektronika ir Elektrotechnika, 2004)
This paper presents the oscillation centre control (stabilisation) problems of the oscillating motor, which are very relevant for acompressor drive. Mechanical springs are mostly used to stabilise the oscillation centre, but this solution makes the drive moreexpensive and unreliable. An analysis of the mathematical model of oscillating synchronous pulsating current motor shows that thelimitation and electrical control of oscillation centre drift can be realised by thyristor control for this type of motor. So, it is possible tocreate springless compressor with sensorless control of oscillation centre according to direct-current component by using complexcontrol algorithm. Some results of numerical simulation of the oscillating motor-compressor mathematical model are corroborated byexperiment of the physical model. The importance of oscillation centre control of oscillating motor-compressor is illustrated as well. Ill.9, bibl. 6 (in Lithuanian; summaries in Lithuanian, English, Russian).